Barriers and benefits of transitioning to an equitable open access model: interviews with LIS journal editors - Teresa Schultz; Rachel Borchardt; DeDe Dawson (Insights: The UKSG Journal)
Not all library and information science (LIS) journals operate under an equitable open access (OA) model, despite librarianship’s emphasis on OA as a value. A previous study illuminated significant barriers for journal editors in transitioning to an equitable OA model. This follow-up study sought, through structured interviews with editors of unflipped journals, to further explore these barriers in order to identify themes and potential solutions to overcome barriers. LIS journal editors who oversaw a transition to equitable OA models were also interviewed regarding the process and impact of flipping the journal. Through qualitative analysis of these interviews, several themes emerged. Barriers to flipping include lack of individual or journal-level agency and motivation, as well as competing priorities for the editors, journal or organization. Benefits to flipping included better alignment of personal and organizational values, increases to perceived prestige and lack of membership disruption for professional societies. Analysis also demonstrated ways in which barriers to flipping differ between professional society journals and large for-profit publisher journals. Based on the analysis, several next steps were identified to better support LIS and other journal editors, as well as potentially move toward solutions to successfully transition more journals in the future.